l.240 ADAPTABILITY AND STABILITY OF Coffea arabica LINES IN THE WESTERN AMAZON - Souza, Carolina Augusto de; Teixeira, Alexsandro Lara; Torres, Josemar Dávila; Silva, Camila Andrade; Espindula, Marcelo Curitiba; Rocha, Rodrigo Barros (Coffee Science - ISSN 1984-3909, 2019)
Growing Coffea arabica in regions of the Western Amazon is limited by early maturation and by its limited adaptation to regions of low altitude and high temperature. The aim in this study was to quantify the genotype × environment interaction of C. arabica lines in four different environments of the Western Amazon, seeking to assist selection of new lines with greater adaptability and stability for the region. In the months of December 2012 and January 2013, four competitive trials were set up in municipalities of the states of Rondônia and Acre. Each trial was composed of 21 lines and 4 reference cultivars evaluated as controls recommended for planting in the southeast region. In combined analysis, significant differences were not detected between the cultivars and controls; the mean yield of hulled coffee was 12.05 bags ha-1. The Alta Floresta Do Oeste environment has higher yield and is the only environment favorable for growing C. arabica; that environment is differentiated from the others through its higher altitudes and low temperatures. Through GGE biplot analyses, lines 12 and 13, identified as H514-7-10-6-9 and H514-7-10-6-2-3-9, were found to have results superior to the controls in the municipality of Alta Floresta Do Oeste, RO. The gain from selection of 56% obtained from line G12 and the gain of 46% obtained from line G13 show performance superior to the best control. The germplasm studied does not have genetic variability that contributes to selection of plants for adaptation to the low altitude and high temperatures in the amazonic region.